(Production Biodiesel of Used Cooking Oil by Using Palm Sugar Bunches Ash as Catalyst) - Alamsyah, Rizal; Hawani Lubis, Enny; Heryani, Susi (Warta Industri Hasil Pertanian, 2010)
Research on production of used cooking oil by using palm sugar bunches ash as catalyst has been conducted. This research was aimed at investigating to the variation of transesterification time (2,3 and 4 hours) by adding 5% palm sugar bunches ash catalyst. The result of transesterification show the use of palm sugar bunches which is uncomposted give better result than the used of composted in tern of kinematic viscosity value. For other parameter (acid value, glycerol total contain, ester value) using either composted or non composted give biodiesel that meet biodiesel requirement No. 04-7182-2006. Based on the research, it could be concluded that 2 hours transesterifikation using non composted catalyst give biodiesel requirement whit yield of metil ester 87,90% and acid value 0,73 mg KOH/g, kinematic viscosity 2,39 cSt, glycerol total contain 0,128 (%b/b) and aster content 98,72 (%b/b). While a composted catalyst give kinematic viscosity value between 1,69 - 1,98, that is not meet biodiesel requirement (2,3 - 6,0 cSt).